ULTRASTRUCTURE OF PINEAL GLAND TUMOR IN WHITE RAT - Abd alsamad, M. A.; Hadi, A. E.; Mohammed, Y. J.; Hasan, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Tumors of pineal gland are very rare brain lesion in the rats and other species like humans. Neoplasms of pineal gland should be included in the possible differential diagnosis list for brain tumor, This type happened when the tumor is sited in the pineal body region. Research scientific investigation of pineal glands of rats being of important from the scientific point view, Transmission electron microscopic study of old and young rats was done to study the pineal gland associated with aging, these  changes characterized by presence of fat like droplet in cytoplasm. Furthermore in the terminal end pinealocytes which were synapsis like associated with the presence of core vesicles containing neurotransmitter like in consistency.